2013
DOI: 10.1155/2013/593274
|View full text |Cite
|
Sign up to set email alerts
|

General Solutions of Fully Fuzzy Linear Systems

Abstract: We propose a method to approximate the solutions of fully fuzzy linear system (FFLS), the so-calledgeneral solutions. So, we firstly solve the 1-cut position of a system, then some unknown spreads are allocated to each row of an FFLS. Using this methodology, we obtain some general solutions which are placed in the well-known solution sets like Tolerable solution set (TSS) and Controllable solution set (CSS). Finally, we solved two examples in order to demonstrate the ability of the proposed method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…Also, our proposed solutions are plotted simultaneously to compare with Dehghan's method (DHG) which is suggested in [19] and Allahviranloo's method (AM) which is proposed in [22]. For more detail see Figs.…”
Section: Proposition 33 Let Us Consider the Solution Of Crisp Systementioning
confidence: 99%
See 2 more Smart Citations
“…Also, our proposed solutions are plotted simultaneously to compare with Dehghan's method (DHG) which is suggested in [19] and Allahviranloo's method (AM) which is proposed in [22]. For more detail see Figs.…”
Section: Proposition 33 Let Us Consider the Solution Of Crisp Systementioning
confidence: 99%
“…In this section, we take an example which has been solved in [22,19] with their methods. However, we adopt the proposed method to solve it to determine four types of solutions which are as bounded solutions while two of them are the maximal symmetric solution and the minimal symmetric solution of the original FFLS.…”
Section: Numerical Examplementioning
confidence: 99%
See 1 more Smart Citation
“…We illustrate the applicability of the previous results by calculating a pair of eigenvalues and eigenvectors to a particular example, choosing a matrix taken from [1,5,6] where it was solved a certain fully fuzzy linear system related. ) .…”
Section: Numerical Examplementioning
confidence: 97%
“…Rao and Chen [24] considered the numerical solutions of FLSs in engineering analysis. Allahviranloo et al proposed the fuzzy symmetric solutions and other algebraic solution for fuzzy linear systems [6,11], and the solutions of fully fuzzy linear systems [8,9,10,12,18,19,23]. Friedman et al [21] suggested a general model for solving a class of n × n FLSs        a 11 x 1 + a 12 x 2 + · · · + a 1n x n = y 1 ,…”
Section: Introductionmentioning
confidence: 99%